Proceedings of the 2014 International Conference on Management, Education and Social Science 2014
DOI: 10.2991/icmess-14.2014.13
|View full text |Cite
|
Sign up to set email alerts
|

Study on Vocabulary Learning Strategies for Chinese English-Majors

Abstract: This paper attempts to explore the overall pattern of English vocabulary learning strategies used by some Chinese English-majors. In addition, both similarities and differences in English vocabulary strategies used between male English-majors and female English-majors. 105 first-year English-majored students from Yangtze University participated in a vocabulary test, band3 test and a questionnaire. The results show: (1) Chinese English-majors used a variety of English vocabulary learning strategies in vocabular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 6 publications
0
5
3
Order By: Relevance
“…Similarly, Al-Khasawneh (2012) also found these strategies were the second least used among Jordanian students with a mean score of 2.68 mean score. However, the use of cognitive strategies was found to be moderate among Moroccan (Ghouati, 2014) and Chinese (Lou, 2014) EFL learners with a percentage of 22.04% and a mean score of 3.30, respectively. In contrast, Komol and Sripetpun (2011) showed that these strategies were highly used by Thai students, with a mean score of 3.20.…”
Section: Cognitive Strategiesmentioning
confidence: 86%
See 4 more Smart Citations
“…Similarly, Al-Khasawneh (2012) also found these strategies were the second least used among Jordanian students with a mean score of 2.68 mean score. However, the use of cognitive strategies was found to be moderate among Moroccan (Ghouati, 2014) and Chinese (Lou, 2014) EFL learners with a percentage of 22.04% and a mean score of 3.30, respectively. In contrast, Komol and Sripetpun (2011) showed that these strategies were highly used by Thai students, with a mean score of 3.20.…”
Section: Cognitive Strategiesmentioning
confidence: 86%
“…Similarly, Lou (2014) showed that these strategies were the most frequently utilized among Chinese students (mean = 3.57). Similarly, Komol and Sripetpun (2011) found that these strategies were found to be common among Thai undergraduates (mean = 3.00).…”
Section: Metacognitive Strategiesmentioning
confidence: 92%
See 3 more Smart Citations